Viewing Woody-Plant Encroachment through a Social–Ecological Lens. (3rd September 2018) - Wilcox, Bradford P; Birt, Andrew; Archer, Steven R; Fuhlendorf, Samuel D; Kreuter, Urs P; Sorice, Michael G; van Leeuwen, Willem J D; Zou, Chris B
Abstract: Grasslands and savannas worldwide have been dramatically altered by woody-plant encroachment (WPE). Maintaining remnant grasslands and restoring degraded grasslands for the people and animals that depend on them will require a new paradigm for WPE, one that views WPE as a complex social–ecological system. Here, we examine WPE in this light, using a conceptual framework designed to bridge the biophysical and social domains. On the basis of this press–pulse WPE framework, we develop a set of integrative hypotheses and identify key knowledge gaps using the Southern Great Plains as a case study. An alternative—and potentially complementary—approach to the press–pulse WPE framework is that of classical dynamic systems modeling, which has been widely adopted in ecology and economics. The explicit coupling of the press–pulse WPE framework with dynamic systems modeling has the potential to yield new insights for understanding the local- to regional-scale processes that drive and constrain changes in grass–woody plant abundances and for predicting the socioeconomic and ecological consequences of these changes.